Women Archaeologists. A Long Fight Against Invisibility: Dorothy Garrod, Gertrude Caton‑Thompson, Virgínia Rau: DOI: 10.5281/zenodo.15005719 - Melo, Ana Ávila de (Estudos Arqueológicos de Oeiras, 2025)
Gender Studies in Archaeology and other scientific domains have stressed, over the last three decades, that Women, as much as men, have also developed an important role in all scientific subjects, but the awareness of this fact is far from having the same impact and recognition as the achievements of their male colleagues. This article wants to emphasize the important work of two Women Archaeologists from the United Kingdom - Dorothy Garrod and Gertrude Caton-Thompson - who developed the main part of their work until the first half of the 20th century. The third case study will present a remarkable Portuguese medievalista - Virgínia Rau - who wanted to be archaeologist, but couldn’t achieve her aim. In order to understand the scientific work of these three women, the geographical, social and economic context of their backgrounds will be described, to help understanding their exceptional scientific work.